Rice farmers and climate change: a vulnerability study and adaptation strategy in Deli Serdang Regency - Herlyna Novasari Siahaan; Mia Wananda Varwasih; Hendris Syah Putra; M. Fariz Afif Hasibuan (Journal of Agricultural Socio-Economics (JASE), 2026)
Rice is a strategic commodity for national food security; however, its production is increasingly threatened by climate change, including shifting rainfall patterns, rising temperatures, and more frequent extreme weather events that create yield uncertainty and reduce farmer welfare. This study aims to analyze the influence of economic, social, and environmental factors on livelihood sustainability and the adaptive capacity of rice farmers in Deli Serdang Regency. The main contribution of this research lies in explicitly modeling livelihood sustainability as a mediating variable linking climate change impacts to farmers’ adaptive capacity within an integrated SEM-PLS framework. Unlike previous studies that mainly focus on direct effects, this study examines both direct and indirect relationships, providing a clearer understanding of how environmental pressures translate into adaptive outcomes at the household level. A quantitative approach was employed using data from 95 rice-farming households. The SEM-PLS results indicate that environmental factors significantly affect livelihood sustainability and adaptive capacity. Livelihood sustainability also significantly enhances adaptive capacity, confirming its role as a key mediating variable. In contrast, economic and social factors do not show significant effects. The model demonstrates moderate explanatory power (R² = 0.389). These findings highlight that adaptation is not solely a direct response to environmental stressors but is strongly mediated by livelihood sustainability, emphasizing the importance of strengthening livelihoods as a central strategy in climate change adaptation policies.